2012
DOI: 10.2147/ijn.s25468
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine for glaucoma: liposomes provide sustained release of latanoprost in the eye

Abstract: Purpose: To report the development and therapeutic evaluation of a liposomal nanocarrier for sustained release of latanoprost, in the rabbit eye. Methods: We fabricated latanoprost-loaded egg-phosphatidylcholine (EggPC) liposomes using the film hydration technique. The delivery vehicles were nano-sized (Z avg = 109 ± 18 nm), had a narrow poly dispersity index (PDI = 0.19 ± 0.04), and a very high loading efficiency (94% ± 5%). Based on in vitro data, we evaluated this fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 30 publications
1
89
0
4
Order By: Relevance
“…Subconjunctival implantation is promising because it has been shown to be safe and efficacious in animal trials, 17,18 and may revolutionize the chronic problem of poor patient adherence. Patient acceptance, therefore, is a crucial component for its implementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subconjunctival implantation is promising because it has been shown to be safe and efficacious in animal trials, 17,18 and may revolutionize the chronic problem of poor patient adherence. Patient acceptance, therefore, is a crucial component for its implementation.…”
Section: Discussionmentioning
confidence: 99%
“…9 There is increasing global recognition of the challenges faced in optimal drug delivery for glaucoma management. A review of the current literature revealed various novel drug delivery systems being developed, including liposomes [10][11][12] and nanocapsules, 13 molecularly imprinted contact lenses, 14 microelectrochemical system (MEMS) drug pumps, 15 and subconjunctival injectable implants. 16 All of these aim to improve therapeutic efficiency of drugs delivered to the eye and reduce reliance on patient compliance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data are expressed as mean±SD for n=5 lower in Brz-LPs group at any time point from 2 to 10 h than Brz-Sus group (p<0.05). The higher ocular hypotensive effect produced by Brz-LPs attributed to the fact that liposomes had a higher binding affinity to the corneal surface than Brz-Sus (27), which caused better absorption of Brz. The pharmacokinetic study of Brz-LPs is in progress to further explain the mechanism of lowering IOP.…”
Section: In Vivo Iop-lowering Effectmentioning
confidence: 99%
“…1 It is commonly considered as the second leading cause of blindness and about 60.5 million individuals have been affected worldwide. 2 High intraocular pressure (IOP) is the main risk factor, which leads to the degeneration of axons from the retinal ganglion cells. Therefore, many kinds of IOP lowering medications are used to manage the disease symptoms, such as timolol, betaxolol, epinephrine, pilocarpine, and dorzolamide.…”
Section: Introductionmentioning
confidence: 99%